Kajian Yuridis Pelaksanaan Adat Seda pada Kasus Kawin Lari - Auliyah, Maulida Fitriya; Ahmad, Muhammad Al Habsy (Jurnal Litigasi Amsir, 2023)
This research aims to determine the implementation of the ’Seda’ custom in cases of elopement/silariang in Bonehau sub-district, Mamuju Regency? And the aim is to find out whether the ’Seda’ custom in cases of elopement/silariang in Bonehau subdistrict, Mamuju district, can be qualified as a customary offense? This research uses Normative legal research methods to outline the legal implications. The results of the research show that the implementation of the Seda custom is still recognized by the community in Mamuju Regency, especially in Bonehau District. Seda custom is one manifestation of customary criminal law. The Seda custom is implemented because the families of those who elope (silariang) consider their actions to be shameful (mepakasiri’). So to restore self-respect or family dignity in community life, the Seda custom is carried out. And Seda’s form of punishment is in the form of physical and non-physical gifts. non-physical, for example, humiliation, being expelled from the village, and being ostracized from society, especially their families. Meanwhile, physical, for example, light abuse, serious abuse and even murder if the violation is very serious. In practice, the Seda custom is carried out in groups (Seda), with the rule that those who are allowed to perform Seda are people.